1995
DOI: 10.1007/bf01980491
|View full text |Cite
|
Sign up to set email alerts
|

Eating and emotional disorders in adolescent obese girls with insulin-dependent diabetes mellitus

Abstract: Adolescent IDDM girls are at increased risk of eating and emotional disorders. Obesity appears to be an important factor for psychiatric complications; more obese IDDM girls suffered from eating disorders NOS sub-clinical bulimia), dysthymia, anxiety disorders, depression and low self-esteem (Family Satisfaction SEI sub-score) than did non-obese IDDM girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 31 publications
1
19
1
1
Order By: Relevance
“…In addition, subthreshold ED were more common in male diabetic adolescents than in non-diabetic peers (García-Reyna et al, 2004). In a meta-analysis by Mannucci et al (Mannucci et al, 2005), they found that the prevalence of AN in type 1 diabetes was not significantly different from that in controls, being 0.27 vs. 0.06 %, respectively, while the prevalence of BN was 1.23 vs. 0.69 %, respectively, p < 0.05, in line with previous studies (Affenito et al, 1997;Jones et al, 2000;Vila et al, 1995). The cited data indicate that young type 1 diabetic patients have a higher prevalence of BN, EDNOS and subthreshold ED than their non-diabetic peers.…”
Section: Clinical Forms Of Eating Disorders In Type 1 Diabeticssupporting
confidence: 72%
See 2 more Smart Citations
“…In addition, subthreshold ED were more common in male diabetic adolescents than in non-diabetic peers (García-Reyna et al, 2004). In a meta-analysis by Mannucci et al (Mannucci et al, 2005), they found that the prevalence of AN in type 1 diabetes was not significantly different from that in controls, being 0.27 vs. 0.06 %, respectively, while the prevalence of BN was 1.23 vs. 0.69 %, respectively, p < 0.05, in line with previous studies (Affenito et al, 1997;Jones et al, 2000;Vila et al, 1995). The cited data indicate that young type 1 diabetic patients have a higher prevalence of BN, EDNOS and subthreshold ED than their non-diabetic peers.…”
Section: Clinical Forms Of Eating Disorders In Type 1 Diabeticssupporting
confidence: 72%
“…The relationship between higher weight and DEB presents a management dilemma for clinicians, since both dietary restraint and higher weight are clear risk factors for the development of ED and their negative health consequences. Although until recently it has been unclear whether there is a specific association of eating disorders with diabetes, some studies have suggested an increased incidence of eating disorders in young women with diabetes (Birk & Spencer, 1987;Engstrom et al, 1999;Hudson et al, Lloyd et al, 1987;Rodin et al, 1985;Rodin et al, 1986Rodin et al, /1987Rodin et al, 1991;Rosmark et al, 1986;Stancin et al, 1989;Steel et al, 1987;Vila, et al, 1993;Vila et al, 1995) whereas others did not find such an increase Fairburn et al, 1991;Friedman et al, 1995;Mannucci et al, 1995;Marcus et al, 1992;Meltzer et al, 2001;Powers et al, 1990;Robertson & Rosenvinge, 1990;Striegel-Moore et al, 1992;Wing et al, 1986). However, the conclusions of these studies are limited by the small sample sizes of females in the age of the highest risk for eating disturbances, the absence of control groups, their low statistical power, and/or by the lack of structured diagnostic interviews for the assessment of eating disorders.…”
Section: Inadequate Coping Attitudes In Type 1 Diabetic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many youth with Type 2DM are obese, and obesity may play a role in the development of depression [22][23][24] . In addition, negative body image and weight concerns have been associated with subsequent depression in girls in several studies 25 .…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…Gender, especially in the period of adolescence, is also a factor. Girls are more prone to and manifest depression symptoms 30 , in respect to boys, although the evidence is still contradictory 8 . Research suggests that girls tend to report more anxiety, depression and internal distress symptoms 10 .…”
Section: Age and Gendermentioning
confidence: 99%